Mathematical Modelling of Water Soil Erosion and Sediment Yield in Large Catchments - Ma, Ning (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2006.